2022
DOI: 10.1007/s11270-022-05542-8
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Fecal Indicators and Microbial Source Tracking Markers in Water Flushed from Riverbank Soils

Abstract: Sewer overflows and exfiltration can potentially contaminate water bodies with pathogens from wastewater. Microbial source tracking (MST) methods such as the detection of the HF183 gene target of Bacteroides have been proposed to monitor human fecal pollution inputs to surface waters; however, the persistence of HF183 and other MST markers in water flushed from soils after contamination events is not well understood. In this study, the persistence and decay of two culture-based fecal indicators, Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
0
11
1
Order By: Relevance
“…Past studies 22,60−62 expressed the challenges associated with teasing apart the relative contributions of different sources of human fecal pollution, such as untreated wastewater and runoff from open defecation. However, this study and Calderon et al 23 showed that there are distinct differences between wastewater and open defecation contributions to runoff in terms of the relative amount of microbial and chemical source tracking markers with contrasting levels of persistence. In untreated wastewater, E. coli, enterococci, HF183, and PMMoV are generally found in high concentrations (Table 2).…”
Section: Microbial and Chemicalcontrasting
confidence: 55%
See 2 more Smart Citations
“…Past studies 22,60−62 expressed the challenges associated with teasing apart the relative contributions of different sources of human fecal pollution, such as untreated wastewater and runoff from open defecation. However, this study and Calderon et al 23 showed that there are distinct differences between wastewater and open defecation contributions to runoff in terms of the relative amount of microbial and chemical source tracking markers with contrasting levels of persistence. In untreated wastewater, E. coli, enterococci, HF183, and PMMoV are generally found in high concentrations (Table 2).…”
Section: Microbial and Chemicalcontrasting
confidence: 55%
“…22 Without exposure to sunlight, fecal indicator bacteria (FIB) and nucleic acids from microbial markers HF183 and pepper mild mottle virus (PMMoV) from untreated wastewater can persist in dry soil for months, and water flushed from soils contaminated by sewage may continue to be sources of contamination long after a spill or leak has occurred. 21,23 Septic tanks are another potential source of human fecal contamination in San Diego, where there are >17,000 septic tanks in use in the San Diego River watershed. 24 Homeless encampments have been considered to be another potential surface contributor of microbial contamination in urban streams 24 due to the lack of sanitation systems available to people experiencing homelessness, which often leads to open defecation in river margins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 The concentrations of E. coli at the Radio Club site ranged from <100 MPN/100 mL to as high as 1.0 × 10 6 MPN/100 mL and were sometimes similar to concentrations measured in raw wastewater in the region, which on average is 2.2 × 10 7 MPN/100 mL. 42 The lower FIB concentrations at Boca Rio may be due to dilution of riverine water by flood tide flows and the mixing of seawater in the tidal zone at the river mouth. Electrical conductivity and TDS concentrations ( Table S1 ) at the Boca Rio site, which are orders of magnitude higher than those at the Radio Club site and similar to values found in seawater, are evidence of the tidal influence at this site.…”
Section: Resultsmentioning
confidence: 85%
“…Long-term soil sampling and analyses for E. coli and wastewater micropollutants can detect the defects and quantify the sewer leakage for dry and wet weather conditions (Guérineau et al 2014). By applying microbial source tracking (MST) and soil sampling, Calderon et al (2022) were able to identify human fecal pollution in soil which is a potential source of microbial pollution to surface and subsurface water as they can last for several months after the contamination. Overall, discussed methods in Tier-II (see Table 2) would provide a deeper and more detailed understanding of the leakage on an intermediate scale, which further needs to be examined with in-sewer inspection methods offered in Tier-III.…”
Section: Soil Samplingmentioning
confidence: 99%